Miniature plankton columns to study the depth distribution of zooplankton at gradients of food, predation risk, temperature, and UV radiation. (26th December 2015) - Maszczyk, Piotr
Abstract: The aim of this study is to describe a novel and comprehensive small‐scale experimental system consisting of twin vertical columns used to study the depth selection of planktonic animals. The system allows simultaneous observations to be made of changes in depth distribution at individual and population levels with minimized constraints restricting the movements of an individual, compared to earlier efforts with other miniaturized experimental systems. It also secures constant and reproducible vertical gradients of temperature, visible light, UV radiation, algal concentrations, and light intensity and spectrum in the visible range. This system mimics a natural combination of field conditions, albeit at a diminished scale, with each gradient independently of the others. The research capability of the system is demonstrated by the preliminary results of a simple experiment in which the depth distribution of a group of Daphnia and the depth selection by a single Daphnia in each of the four gradients was recorded.